Efeitos da cafeína na foliculogênese, desenvolvimento placentário e em parâmetros reprodutivos, biométricos e comportamentais transgeracionais em modelo murino. - Thaís de Mérici Domingues e Paula (2023)
Caffeine is a substance commonly consumed by pregnant and lactating women and, due to its ability to cross the placental membrane and accumulate in the fetal body, as well as to be secreted into breast milk, its consumption has been contraindicated or suggested in minimal doses during pregnancy and lactation. Studies in humans and rodents have linked caffeine consumption to lower rates of fertilization, embryo implantation, alterations in placental structure, increased occurrence of low fetal and placental weight, abortions, and stillbirths. Although it presents such deleterious effects, to date there is a paucity of data describing the mechanisms of reproductive, behavioral, and functional changes consequent to chronic maternal caffeine consumption during pregnancy and lactation. Additionally, it becomes necessary to investigate whether such effects will also manifest in subsequent generations. Therefore, the objective of this study was to evaluate the biometric, reproductive, morphofunctional, and behavioral changes in two generations of iso- and heterozygous mice, resulting from daily maternal consumption of caffeine during gestation and/or lactation. One hundred and twenty adult female Swiss mice and 15 female Black-6 mice were subjected to four separate experiments involving the consumption of varying doses of caffeine (0, 60, 120 or 240 mg/caffeine/day) before and during gestation and/or lactation of F1 and F2 offspring. Histological, hormonal, immunohistochemical and behavioral analyses were performed on the different groups of mice and their offspring throughout their growth and adult life. The results showed that, even at currently recommended doses, caffeine caused alterations in the estrous cycle and follicular reserve of the animals; intrauterine growth restriction, alterations in placental morphology and morphometry; impaired biometric and sexual development of F1 and F2 offspring; and cognitive and behavioral alterations of F1 and F2 offspring, especially of females. These results indicate that the current recommended doses of caffeine consumption need to be reviewed and updated in humans, especially those related to lactation, which are little discussed and referenced.